Agro food by-products and essential oil constituents curtail virulence and biofilm of Vibrio harveyi. (October 2019) - Sowndarya, Jothipandiyan; Farisa Banu, Sanaulla; Madhura, Gunasekaran; Yuvalakshmi, Prabakaran; Rubini, Durairajan; Bandeira Junior, Guerino; Baldisserotto, Bernardo; Vadivel, Vellingiri; Nithyanand, Paramasivam
Abstract: Vibrio harveyi causes severe loss to the aquaculture industry due to its virulence, which is mediated by Quorum sensing (QS) and biofilm formation. In the current study, we have explored the anti-virulent properties and biofilm disruption ability of luteolin (extracted from coconut shell) and linalool against this important aquaculture pathogen. HPLC analysis of the methanolic extract of coconut shells revealed a single major peak which matched to the standard luteolin which was further elucidated by NMR studies. Further, luteolin and linalool were screened for their ability to inhibit biofilms and various quorum sensing mediated virulence factors of V. harveyi . The Minimum Inhibitory Concentration (MIC) of the two compounds was determined and the sub-inhibitory concentrations of the compounds were able to inhibit biofilm formation. Both the compounds disrupted about 60–70% mature biofilms, which was also visually observed by light microscopy. Both linalool and luteolin exhibited a significant reduction in the production of EPS and alginate in the biofilms matrix of V. harveyi which was confirmed by Scanning Electron Microscopy (SEM). Both compounds inhibited the swarming and swimming motility, the crucial quorum sensing (QS) mediated virulence of V. harveyi . The present study shows the presence of valuable polyphenolic compound like luteolin in coconut shells that are discarded as a waste. From the present study we envisage that luteolin and linalool can serve as potent anti-virulent agents to combat QS mediated infections against aquaculture pathogens. Highlights: Natural compounds have been sought to treat biofilm mediated infections. Coconut shell contains luteolin, which possess antibacterial activity. Luteolin and linalool disrupted Vibrio harveyi mature biofilms. Both compounds possess antivirulent properties and may be used in aquaculture.